VARIABILITY IN STEROL FLUX IN THE ICE-COVERED LAGOON SAROMA KO, HOKKAIDO, JAPAN (Eleventh Symposium on Polar Biology) - ササキ, ヒロシ; ヤマグチ, トシヤス; ワタナベ, ケンタロウ; タニムラ, アツシ; フクチ, ミツオ; SASAKI, Hiroshi; YAMAGUCHI, Toshiyasu; WATANABE, Kentaro; TANIMURA, Atsushi; FUKUCHI, Mitsuo (National Institute of Polar Research, 1990)
P(論文) A time-series sediment trap was deployed in a shallow lagoon, Saroma Ko, from 9 December 1986 to 2 May 1987. During the ice-covered period (mid-January to mid-April) total mass fluxes (dry weight) were lower than 2 gm^<-2> day^<-1>, while after mid-April the flux increased to more than 11 gm^<-2> day^<-1>. The dominant sterol associated with sinking particles throughout the observation period was cholesterol most of which were possibly from animal-derived sources such as scallop feces. During the ice-covered period, sterols mostly were derived from marine animals, although the sterol abundance was low in quantity. The period of phytoplankton bloom below the ice (mid-March to mid-April) did not respond to that of the maximum flux (after mid-April), but coincided with that of the occurrence of phytoplankton-derived sterols. During the ice-free periods (before mid-January and after mid-April), sinking particle sources are variable, and bottom sediment- and land-derived (mostly terrestrial plants) sterols are larger in quantity than those during the ice-covered periods, primarily because of the active water movements in the lagoon. departmental bulletin paper